2009
DOI: 10.1039/b909360e
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic amide formation with α′-hydroxyenones as acylating reagents

Abstract: Abstractα′-Hydroxyenones undergo clean, catalytic amidations with amines promoted by the combination of an N-heterocyclic carbene and 1,2,4-triazole.The ubiquity of amide-containing organic compounds coupled with the generally expensive and wasteful methods for their formation have engendered intense, recent efforts in the identification and development of catalytic methods for amide-bond formation. 1 The most attractive approach, the direct catalytic coupling of carboxylic acids and amines, 2 can be achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…178,206 A wide variety of aromatic and heteroaromatic substituents are tolerated as reaction partners for annulation with vinylogous amides. The product 3,4-dihydropyridinones are isolated in good-to-excellent yields (59–99%).…”
Section: Catalysis Involving Acylazolium Intermediatesmentioning
confidence: 99%
“…178,206 A wide variety of aromatic and heteroaromatic substituents are tolerated as reaction partners for annulation with vinylogous amides. The product 3,4-dihydropyridinones are isolated in good-to-excellent yields (59–99%).…”
Section: Catalysis Involving Acylazolium Intermediatesmentioning
confidence: 99%
“…Bode and coworkers subsequently found that α-hydroxyenones could be used as masked N-acylating agents for both primary and secondary amines using an NHC and 1,2,4-triazole as a cocatalyst (Figure 62(c)). 383 Addition of NHC to an α-hydroxyenone promotes a retro-benzoin reaction that releases acetone, with the resulting Breslow intermediate then undergoing an imidazole-mediated redox amidation reaction. In 2012, Yamada and coworkers employed an NHC catalyst in conjunction with N-chlorosuccinimide (NCS) as an oxidant in the presence of HOBT to form secondary and tertiary amides from unfunctionalized aldehydes.…”
Section: Redox Amidation Reactionsmentioning
confidence: 99%
“…389 The potential of this approach has been demonstrated further by Barbas Carbene catalyst Figure 62 NHC-mediated protocols for the catalytic redox N-acylation of amines. [381][382][383][384][385] and TBHP in ethyl acetate to prepare NHS esters in situ, which could be intercepted by amines to afford their corresponding amides in good yield. 390 Other protocols that are proposed to proceed via free-radical intermediates using aldehyde donors have also been developed, including catalytic systems such as FeCl 3 /TBHP, 391 and the use of diacetoxyiodobenzene in the ionic liquid BMIMBF 4 .…”
Section: Redox Amidation Reactionsmentioning
confidence: 99%
“…Further work in this area by the Bode group has revealed that α‘ -hydroxy enones 88 obtained from aldehydes are also competent substrates with substoichiometric quantities of 1,2,4-triazole to provide saturated amide products 84 in 47-99 % yield (Scheme 21, b). [31] The reaction proceeds through a retro-benzoin reaction catalyzed by 55 and base to liberate acetone and give the Breslow intermediate 91 (Scheme 21, c). This then continues to the redox pathway to provide product.…”
Section: Nhc Redox Acylationmentioning
confidence: 99%